Clinical seizure manifestations in the absence of synaptic connections. Issue 1 (30th March 2021) - Macdonald‐Laurs, Emma; Bailey, Catherine A.; Barton, Sarah; Yang, Joseph Yuan‐Mou; Mandelstam, Simone; Macgregor, Duncan; Lockhart, Paul J.; Leventer, Richard J.; Maixner, Wirginia J.; Harvey, A. Simon
Abstract: We report a child with a history of temporal‐parietal‐occipital disconnection for epilepsy secondary to posterior quadrantic dysplasia who developed recurrent and prolonged bouts of distress and autonomic disturbance associated with EEG and PET evidence of status epilepticus confined to his disconnected cortex. These bouts were refractory to antiseizure medications but resolved following resection of the disconnected cortex. In the absence of synaptic connections, we hypothesise that his seizure‐related symptoms were mediated either by neurochemical transmission in preserved vascular and lymphatic channels or by ephaptic transmission to trigeminal nerve fibres in overlying dura, producing symptoms akin to migraine. The case highlights potential means by which seizures may manifest clinically, without synaptic connections, and adds to the differential for symptoms post‐disconnection surgery.